The human cell atlas of the hypertrophic heart reveals impaired inter-cellular cross-talks. (14th October 2021) - Nicin, L; Bruening, R S; Kattih, B; Glaser, S F; Abplanalp, W T; Schroeter, S M; Arsalan, M; Holubec, T; Emrich, F; Meder, B; Reich, C; Walther, T; et al.
Abstract: Introduction: The pathophysiology of cardiac hypertrophy is multifactorial and is accompanied by the dysregulation of various signaling pathways contributing to cardiac dysfunction and heart failure. While the hypertrophic response of cardiomyocytes (CM) has been extensively studied, the interplay of CMs with the non-parenchymal cells in the heart is less explored. Here, we apply high-resolution transcriptomic analysis on single cell level allowing the identification of cellular responses and communication in the hypertrophic human heart. Results: We analyzed single nuclei RNA sequencing data of cardiac tissues from five patients with aortic stenosis and cardiac hypertrophy and 13 matched healthy subjects. Bioinformatic data analysis of 88, 536 nuclei followed by clustering led to the identification of specific heterogenic cell type signatures. Analyzing cell type specific gene expression signatures, we found the expected up-regulation of the cardiac stress MYH7 (4.15-fold), CMYA5 (4.89-fold) and XIRP2 (6.13-fold) in cardiomyocytes (CM) (all p<0.0001). Fibroblasts showed increased expression of genes associated with fibrosis and activation markers such as periostin (POSTN; 6.84-fold, p<0.0001). In-silico analysis of intercellular communication pathways revealed a striking downregulation of ligand-receptor interactions between CMs and other cells in hypertrophic compared to healthy controls indicating that CMs are less responsive to signals from fibroblasts and endothelial cells (ECs) in the hypertrophied heart. Particularly, CM showed reduced expression of receptor tyrosine kinases of the Ephrin family and FGF-family members. Specifically, Ephrin-B1 was significantly downregulated in CMs of the hypertrophic hearts (0.01-fold, p<0.0001). The down-regulation of Ephrin-B1 was additionally validated on protein level using histological sections of hypertrophic cardiomyopathy patients (n=6) versus healthy controls (n=5) (0.66-fold, p=0.02). In-vitro studies in neonatal cardiomyocytes further demonstrated that activation of the Ephrin-B1 receptor by the agonist Ephrin-B2 induced cardioprotective effects. Thus, Ephrin-B2 inhibited phenylephrine (PE) induced Nppb expression by 0.775-fold (vs. PE) and hypertrophic growth (0.774-fold reduction of cell size vs. PE). Similar findings were observed in PE-stimulated human cardiac organoids, which showed a 0.58-fold reduction of size in response to Ephrin-B2 treatments compared to PE alone. Conclusion: Investigating the cross-talk in cardiac hypertrophy reveals novel disturbed communication signatures, with a striking reduction in the intercellular communication pathways of CMs. Reduced expression of receptors of the Ephrin family, particularly Ephrin-B1, in CM may prevent cardioprotective signaling by the agonist Ephrin-B2, which is highly expressed in ECs, leading to inhibition of cardioprotective cross-talk between ECs and CMs in the hypertrophic heart. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Dr. Rolf M. Schwiete StiftungDie Deutsche ForschungsgemeinschaftGerman Center for Cardiovascular Research